The anatomy of the musculoskeletal system in the light of Al Quran and hadith - Yusof, Nurul Asyiqin; Che Mohamad, Che Anuar; Hassan, Ahmad Nizam (2016)
The integration and islamicization of human knowledge between the medical and health care sciences with divine knowledge were established since the early time of Ibnu Sina, Arrazi, Ibnu Rusyd, Az Zahrawi and others. However, the glorious period of Islamic medicine gradually disappeared after the period of Abassiyyah and Uthmaniyyah. In today’s modern world, many scholars tend to separate the knowledge of modern medicine with that of the revealed knowledge, in such a way that these two fields do not correlate to one another. There is also paucity in the collections of reference that integrate the Quran and hadith with medicine. Thus, this review was conducted to extract as many sources of Quranic verses and authentic hadith of Prophet Muhammad PBUH that relate to a specific field in medicine: the anatomy of human musculoskeletal system. The human musculoskeletal system is very unique in which it is the ‘backbone’ of normal human posture, where it plays a vital role in maintaining human daily activities. Many Quranic verses and hadith mentioned by Prophet Muhammad are directly related to this system, for example, the number of joints in a human body and its relationship with the prayers (salah) of muslims, the coccyx bone that is indestructible and will be the source for reconstruction of humans during the afterlife, and others. The reference to the human musculoskeletal system from Quranic verses and hadith emphasizes the importance of knowledge in this area of medicine. Thus, further research and scientific studies are needed to better understand the anatomy and functional aspect of the human musculoskeletal system to aid in the prevention and management of musculoskeletal diseases.